O veneno está na mesa 2 - Luiz Claúdio Meirelles (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2015)
Datasheet: Director: Silvio Tendler Production: Maycon Almeida Developer: Caliban Cinema and Content Screenplay: Silvio Tendler Photography: Xeno Veloso Year: 2014 Country Brazil Genre: Documentary Color: Colorful Duration: 71 minutes Available in: http://www.youtube.com/watch?v=fyvoKljtvG4 Accessed on: 26 September 2014